Principal's Strategy in Increasing the Teaching Competency of Non-Bachelor Teachers at MTS Putra TMI Al-Amien Prenduan Sumenep Madura 2023 - A. Nasrullah; Ahmadi, Ahmadi (Values: Jurnal Kajian Islam Multidisiplin, 2025)
The principal plays a crucial role as a leader in guiding teachers, administrative staff, and other school personnel. Based on preliminary observations at MTs TMI Putra Al-Amien Prenduan, the principal has demonstrated an active role in carrying out leadership functions. However, as the majority of teachers at MTs TMI Putra Al-Amien Prenduan hold non-bachelor degrees, there are several challenges in which some teachers have not performed their duties optimally. This condition necessitates the implementation of strategies by the principal to improve teaching competence among teachers. This study aims to identify and describe the principal’s strategies in enhancing the teaching competence of non-degree teachers at MTs TMI Putra Al-Amien Prenduan. The research employed a qualitative field approach, with data collected through interviews, observations, and documentation. The findings reveal six main strategies used by the principal to improve teaching competence among non-degree teachers, six implications resulting from the implementation of these strategies, as well as two supporting and inhibiting factors influencing their execution.